The Elderly in the Eyes of the Youth: Results of Own Research - Pakos, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The article presents the results of own research concerning the way modern youth perceives the elderly. The analysed group was high school students of Lodz and university students. 116 respondents, including 84 women and 32 men participated in the poll research. The research study aimed at diagnosing attitudes towards the elderly among the representatives of Polish youth and, especially, upper secondary and university students. The research results showed the picture of young people whose opinions on the elders vary depending on the particular group they are referring to: the general group of senior citizens or old people they personally know, e.g. their grandparents University students, more than high school students, are willing to notice that Polish society needs the elderly.